The narrative reports’ analysis of 5 year old children after getting aquaired with audiovisual material - Kackieło-Tomulewicz, Justyna; Milewska, Karolina (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
A narrative is a narrative of a series of events that have occurred in the past or are presented as if they had actually happened in the past. In this narrative competence is understood as knowledge about the essence and structure of narrative, about its basic functions and stylistic categories, manifesting itself in complex linguistic skills related to the construction of narrative statements with specific genre features, in accordance with applicable language standards and adequate to the consultation. The aim of the study was to analyze the narrative statements of 5-year-old children after familiarizing themselves with the story once viewed. The specific goal was to check what particular statements of children with proper speech development would characterize, corresponding to the conducted test.